Criteria base of the jet ejector operating process - V. I. Kuznetsov; I. O. Kuznetsova; D. D. Shpakovskiy (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article considers the question of creating a criterion base of the jet ejector operating process on the basis of a closed mathematical model. The basic parameters affecting the degree of ejection and total pressure rise at the discharge from the mixing chamber of the jet ejector are determined. Finding dimensionless complexes using the modeling theory allows determining the criterion base of the operating process of the jet ejector. At full geometrical similarity, without considering heat exchange and using “natural” and “model” gas, the number of similarity criteria is reduced to Reynolds number.